A preliminary assessment of latent fingerprint evidence damage on mobile device screens caused by digital forensic extractions. (December 2018) - Horsman, Graeme; Page, Helen; Beveridge, Peter
Abstract: Mobile devices continue to feature heavily in criminal investigations and often bear multiple forms of potentially relevant evidence. In the context of identifying the owner of a device, both latent fingerprints and resident digital data may be crucial to investigations, yet each individual process may have a detrimental impact on the other. Fingerprint development techniques are known to impact device hardware, whilst digital extraction processes can destroy latent prints. This article examines the impact of mobile device extraction procedures on resident screen fingerprints. The impact of bare fingered, cotton gloved, latex gloved and stylus screen press and swipes on latent print destruction are examined. Results indicate that all forms of interaction cause print damage, but to a variable extent. Provisional device handling recommendations are offered.